High mantle seismic P-wave speeds as a signature for gravitational spreading of superplumes - Stern, Tim (2020)
New passive- and active-source seismic experiments reveal unusually high mantle P-wave speeds that extend beneath the remnants of the world’s largest known large igneous province, making up the 120-million-year-old Ontong-Java-Manihiki-Hikurangi Plateau. Sub-Moho Pn phases of ~8.8 ± 0.2 km/s are resolved with negligible azimuthal seismic anisotropy, but with strong radial anisotropy (~10%), characteristic of aggregates of olivine with an AG crystallographic fabric. These seismic results are the first in situ evidence for this fabric in the upper mantle. We show that its presence can be explained by isotropic horizontal dilation and vertical flattening due to late-stage gravitational collapse and spreading in the top 10 to 20 km of a depleted, mushroom-shaped, superplume head on a horizontal length scale of 1000 km or more. This way, it provides a seismic tool to track plumes long after the thermal effects have ceased.